2019
DOI: 10.1007/s10508-019-01533-9
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Mental Health Problems, Substance Use, Violence, and Related Psychosocial Factors in Transgender, Non-Binary, and Gender Diverse Youth and Young Adults

Abstract: Transgender and gender diverse (TGD) people are disproportionately impacted by various health issues and associated risk factors, but little is known about differences in these outcomes between gender identities within the TGD population. This study characterized the health of a diverse sample of TGD youth and young adults. Data were taken from the baseline visit of two longitudinal studies in the Chicago area, RADAR (N = 1,079, M age = 20.8 years) and FAB 400 (N = 488, M age = 19.57 years), which are cohorts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
161
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(184 citation statements)
references
References 50 publications
17
161
1
5
Order By: Relevance
“…There is a general lack of research on gender norms, roles, relations and cannabis use among non-heterosexual people and people with diverse gender identities. Yet trans and gender-diverse youth report high rates of substance use, mental health issues and violence and trauma, and transgender women and non-binary assigned male at birth youth tend to report greater substance use [62]. Similarly, among young adults, high rates of tobacco use have been reported among both sexual minority females and gender minorities [63].…”
Section: Discussionmentioning
confidence: 99%
“…There is a general lack of research on gender norms, roles, relations and cannabis use among non-heterosexual people and people with diverse gender identities. Yet trans and gender-diverse youth report high rates of substance use, mental health issues and violence and trauma, and transgender women and non-binary assigned male at birth youth tend to report greater substance use [62]. Similarly, among young adults, high rates of tobacco use have been reported among both sexual minority females and gender minorities [63].…”
Section: Discussionmentioning
confidence: 99%
“…18 Certain minority stressors, including a lack of social supports, may be exacerbated due to the pandemic, especially as a result of social distancing, causing an even higher burden of poor mental health in this population. In combination, higher rates of mental and behavioral health concerns and domestic violence affecting SGM people, 13,19,20 the psychological challenges of social isolation, and the traumatic nature of exposure to the COVID-19 pandemic create a potentially devastating constellation of risk for SGM populations. 6,9 Health care systems are, furthermore, ill-equipped to combat these inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on nationally-representative US data, Perez-Brumer et al [ 68 ] found that trans youth had almost three times the odds of reporting past-year suicidal ideation compared to cis youth. Newcomb et al [ 69 ] also examined differences between gender identities in suicidality. The authors found that nonbinary youths assigned male at birth reported the highest rates of suicidal ideation (50.0%), compared to nonbinary youths assigned female at birth (31.7%), as well as trans men (35.7%), or trans women (13.8%) [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newcomb et al [ 69 ] also examined differences between gender identities in suicidality. The authors found that nonbinary youths assigned male at birth reported the highest rates of suicidal ideation (50.0%), compared to nonbinary youths assigned female at birth (31.7%), as well as trans men (35.7%), or trans women (13.8%) [ 69 ].…”
Section: Introductionmentioning
confidence: 99%